Wackestones and grainstones geochemistry from Baturaja Formation, South Sumatra Province, Indonesia : origin and depositional environment - Irzon, Ronaldo; Maryanto, Sigit; Syafri, Ildrem; Kurnia,; Jazuli, Heri Hermianto; Hartanto, Priyo (Penerbit Universiti Kebangsaan Malaysia, 2022)
Limestone members of the Baturaja Formation at Rambangnia Traverse in Sumatra are classified into wackestones, packstones, grainstones, and floatstones based on microfacies discrimination. This study compared the geochemistry characteristics of the wackestones and the grainstones at the traverse to define their material origins and sedimentation environment. A total of ten samples were analyzed using XRF for 11 oxides and 12 trace elements composition. The samples are carbonates with a minimum fraction of dolomite or magnesite. Clastic material of eroded Kikim Formation is the major impurity origin in the limestone without considerable sulfate content. The wackstones signify a higher detrital input rate and contain more clay which increased during CaO separation than the grainstones. Iron in the wackstones was lost through diagenesis while sodium in the grainstones was precipitated directly from seawater. According to V/Cr and Cu/Zn ratios, the wackestones were deposited in more oxic condition than the grainstones. The studied carbonates have not been affected by a considerable post-depositional alteration based on their geochemistry characteristics.